Paper cuts - Adams, Ellery (Adams, Ellery. Secret, Book, and Scone Society novel, 2023)
When Kelly Walsh, the woman her ex-husband left her for, is murdered, bookstore owner and bibliotherapist Nora Pennington and The Secret, Book, and Scone Society seek justice for Kelly amidst gossip and suspicion.